Evaluasi Kesesuaian Dosis dan Interaksi Obat Potensial pada Pasien Gagal Ginjal Kronik di Rumah Sakit Swasta Denpasar Bali - Ratnasari, Pande Made Desy; Dhrik, Mahadri; Rizqy, Laili Kurnia Rizqy; Devi, Ni Kadek Dwi Rosita (Jurnal Ilmiah Medicamento, 2024)
End-Stage Renal Disease (ESRD) is a chronic disease with a high mortality rate and increasing prevalence. Patients often experience complications from hemodialysis (HD) and comorbid conditions, leading to treatment complexity and polypharmacy. These factors increase the risk of drug-related problems, including inappropriate dosing and drug interactions. This study evaluated dose appropriateness and potential drug interactions in ESRD patients. The study employed a cross-sectional design involving 96 ESRD patients at the HD Clinic of a private hospital in Denpasar. Data collection was conducted in May 2021 using a data collection instrument based on medical records and purposive sampling techniques. Inclusion criteria included ESRD patients with or without complications and comorbidities, aged ≥18 years, and receiving ≥3 medications. Pregnant or breastfeeding patients were excluded. Dose adjustments were determined using the Cockcroft-Gault equation and therapeutic guidelines, while drug interactions were assessed using Stockley's Drug Interactions, Drug Interaction Facts, Drug Information Handbook, IBM Micromedex®, and Medscape®. The results showed that most patients were aged 45-59 years (46.88%), male (68.75%), had hypertension complications (42.31%), and had comorbid dyslipidemia (55.56%). Most patients received 5-7 drugs (40.62%), primarily vitamins (18.06%), administered once daily (38.26%) and orally (71.26%). A total of 23 prescriptions (23.96%) required dose adjustment, and 53.12% of prescriptions had potential drug interactions, mainly pharmacodynamic (82.72%), with moderate severity (87.65%) and risk category C (82.72%). Pharmacists' roles in reviewing prescriptions should be enhanced to prevent or minimize drug-related problems.